Superhighway Virtual Track System Based on Intelligent Road Buttons - Yong-Ming He; Yu-Long Pei; Bin Ran; Jia Kang; Yu-Ting Song (IEEE Access, 2020)
To improve the safety of superhighways, a virtual track system for superhighways based on intelligent road buttons is studied by means of a structural analysis and mathematical model. The system consists of a road subsystem, onboard subsystem and service center subsystem. When a vehicle equipped with an onboard subsystem nears the road buttons, they activate the virtual track system, and the reader reads location coordinates and road alignment information at that point from the label buttons. At the same time, the data processing module begins to function. First, the module reads the linear parameters and processes them to obtain the angle between the road tangent and vehicle body. Then, the module reads the angle of the front wheels, the vehicle speed and the distance between the adjacent two label buttons. Finally, the module obtains the rotational speed of the steering wheel while the vehicle is driving between two label buttons by using the computational model and sends the control parameters to the steering motor. The research results show that when the design speed of the superhighway is 140 km/h, 160 km/h and 180 km/h and the distances between the road buttons are less than 1.33 m, 1.50 m and 1.69 m, respectively, the distance between the centerline of the road and the vehicle can be restricted to less than 50 cm. Therefore, the virtual track system based on intelligent road buttons can restrict vehicles to travel in the virtual track and ensure the safety of superhighways.